K-Shell Ionization Cross Sections of Transition and Non Metals by Electron Impacts (Journal of Atomic and Molecular Sciences, 2021)
The theoretical model, developed by Khare, has been modified to calculate the total cross sections for K-shell ionization of 12 atom targets (C, N, O, Al, Fe, Se, Ag, Sb, Ho, Au, Bi, U) due to electron impact at incident electron energy from ionization threshold to 1 GeV. The various calculated cross sections are in remarkable agreement with available experimental data and other theoretical cross sections.